Comparison of different analysis algorithms to calculate multiple-breath washout outcomes. Issue 3 (13th July 2018) - Anagnostopoulou, Pinelopi; Kranz, Nadja; Wolfensberger, Jeremias; Guidi, Marisa; Nyilas, Sylvia; Koerner-Rettberg, Cordula; Yammine, Sophie; Singer, Florian; Latzin, Philipp
Lung clearance index (LCI) is the main outcome of the multiple-breath washout (MBW) test. Current recommendations for LCI acquisition are based on low-grade evidence. The aim of this study was to challenge those recommendations using alternative methods for LCI analysis. Nitrogen MBW measurements from school-aged children, 20 healthy controls, 20 with cystic fibrosis (CF) and 17 with primary ciliary dyskinesia (PCD), were analysed using 1) current algorithms (standard), 2) three alternative algorithms to detect with higher precision the end of MBW testing and 3) two alternative algorithms to determine exhaled tracer gas concentrations. LCI values, intra-test repeatability, and ability to discriminate between health and lung disease were compared between these methods. The analysis methods strongly influenced LCI (mean±sd overall differences (%) between standard and alternative analysis methods: −4.9±5.7%; range: −66–19%), but did not improve intra-test variability. Discrimination between health and disease was comparable as areas under the receiver operator curves were not greater than that from standard analysis. This study supports current recommendations for LCI calculation in children. Alternative methods influence LCI estimates and hamper comparability between MBW setups. Alternative algorithms, whenever used, should be carefully reported. Lung clearance index values are strongly affected by the algorithms used for the analysis http://ow.ly/h2Rs30ktPiN